Rediseño del banco de bombas en serie y paralelo del laboratorio de mecánica de fluidos de la Universidad Antonio Nariño - Padilla Sierra, Hansel David (Universidad Antonio Nariño, 2023)
This document will establish a proposal for the redesign of the bank pumps in series and in parallel from the University Antonio Nariño headquarters Puerto Colombia based in the requirements set forth in the diagnosis mechanical and electrical of the current state of the equipment and the ISO standards for Hydraulic design and code Colombian electricity company NTC 2050 with the purpose of Obtain a functional team that matches the new technologies i.e. with pressure and flow sensors with which they will allow the proper development practices them through the laboratory guides and the test bench operating manual will be in the facilities of the Universidad Antonio Nariño Headquarters Puerto Colombia.